Characteristics of lymph node metastasis in resected adenosquamous lung cancer. Issue 48 (December 2017) - Kong, Min; Jin, Jiang; Cai, Xiuyu; Shen, Jianfei; Ma, Dehua; Ye, Minhua; Zhu, Chengchu; Freedman, Samuel; Walters, Kelly; Xu, Xin; Chen, Baofu
Abstract : Abstract: The aim of this study was to retrospectively analyze the clinical data of resected adenosquamous lung cancer (ASLC) and to explore the influencing factors and clinicopathological characteristics of the metastasis lymph nodes. A total of 1156 consecutive patients with surgically resected lung cancer from January 2009 to June 2014 were studied. Fifty-four previously diagnosed ASLC patients were re-evaluated by experienced pathologists. IHC and H&E staining were employed to examine the primary focus and metastasis lymph nodes. The relationship between lymph node metastasis and clinicopathological characteristics of ASLC patients was then analyzed and the pathological type of metastasis lymph node was also determined. Forty-nine cases of typical ASLC were included in the study. Of the 49 ASLC patients, 26 cases presented lymph node metastasis. Lymph node metastasis was not associated with gender, smoking, tumor distribution, histological type of primary focus, and preoperative CEA level, but was associated with age ≥ 65 ( P  < .05) and tumor size ≥ 3 cm ( P  < .05). Lymph node metastasis adenocarcinoma was the main type in ASLC patients, and was related to the age and tumor size of the primary focus. Further large sample studies are necessary to identify influencing factors and clinicopathological characteristics of metastasis lymph nodes.